Psychological Contract, Self-Efficacy, Job Stress, and Turnover Intention: A View of Job Demand-Control-Support Model - Shao, Lijin; Guo, Hui; Yue, Xiaoyao; Zhang, Zhaohua (Frontiers in Psychology, 2022)
The outbreak of Coronavirus disease 2019 (COVID-19) has caused enterprises to face more challenges, such as operational management, production and sales management, and human resource management, among other issues. In the context of the global knowledge economy, employees with high knowledge and skills have become an important source of corporate growth and breakthroughs. However, employees may intend to transfer to other companies due to the pressure of the external and internal environments, so the main topic explored by this paper will be the change of employees' turnover intention. The purpose of this study was to explore the influence mechanism that propels the employees' self-efficacy, job stress, and turnover intention, and the moderating effect of transformational leadership. A total of 553 valid responses from several information service companies in China are collected via purposive sampling and used in the data analysis. This study conducts partial least squares structural equation modeling partial least squares structural equation modeling (PLS-SEM) to analyze collected data. The results of the path analysis with structural equation modeling show that employees' psychological contracts have a positive impact on the self-efficacy and a negative impact on the job stress. Employees' self-efficacy has a negative impact on job stress and turnover intention; transformational leadership plays a significant moderator in the research framework. Based on research findings, the theoretical and managerial implications are presented.